2016
DOI: 10.1089/vim.2016.0043
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin Receptor Antibody (TRAb)-IgM Levels Are Markedly Higher Than TRAb-IgG Levels in Graves' Disease Patients and Controls, and TRAb-IgM Production Is Related to Epstein–Barr Virus Reactivation

Abstract: Graves' disease is an autoimmune thyroid disorder that mainly presents as hyperthyroidism and is caused by thyrotropin receptor antibodies (TRAbs) that stimulate thyroid-stimulating hormone receptors. We previously reported that Graves' disease patients and healthy controls both had Epstein-Barr virus (EBV)-infected TRAb-positive B cells and the EBV-reactivated induction of these B cells in cultures may induce the production of TRAbs. In the present study, we quantified serum TRAb-IgG and TRAb-IgM levels in 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…In this study, we measured plasma TRAbs with RRA and TRAb-isotype ELISA, which we used in previous studies (6). However, the results obtained did not necessarily correlate, which may be attributed to differences in the detection system between RRA and ELISA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we measured plasma TRAbs with RRA and TRAb-isotype ELISA, which we used in previous studies (6). However, the results obtained did not necessarily correlate, which may be attributed to differences in the detection system between RRA and ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…RRA assesses the inhibition of TSH binding to TSHR by serum TRAbs (3), whereas ELISA evaluates the binding of serum TRAb to recombinant human TSHR (6). The binding of TRAb-IgM to TSHR may be structurally varied (4), and neutral antibody, which is a type of TRAb, may only be measured by ELISA because they do not occupy TSHR (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumata et al recently showed that serum levels of TRAb-IgM were higher than those of TRAb-IgG in patients with Graves' disease and healthy controls, in contrast to serum levels of total-IgG being higher than those of total-IgM (9). Both of these findings support the rescue of autoreactive B cells by polyclonal B cell activation due to EBV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Аутоантитела стимулируют фолликулярные клетки щитовидной железы к выработке избытка гормонов, которые приводят к тиреотоксикозу. Данное положение лежит в основе патогенеза болезни Грейвса и болезни Хашимото [11,36]. Клинические проявления тиреоидита Хашимото обусловлены избытком функционального Toll-подобного рецептора 3, который из-за мутаций в ДНК экспрессирует тиреоциты у пациентов с латентной формой ЭБВИ [31,36].…”
unclassified